1999
DOI: 10.1136/fn.81.2.f134
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal neuroblastoma

Abstract: Over nine years, 33 children with neonatal neuroblastoma were registered with the UKCCSG (United Kingdom Children's Cancer Study Group). Tumours of all stages were found, but stage 4S disease predominated. Five tumours were detected prenatally by ultrasonography. Treatment varied according to tumour stage. The overall survival of the group was 91%. Ten children have had long term complications as a result of their disease, usually as a result of spinal tumour involvement. The good overall prognosis in this age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 20 publications
0
18
0
1
Order By: Relevance
“…[15][16][17][18] In the UK only 33 neonates were identified with neonatal neuroblastoma between 1986 and 1994, most of whom had stage 4S disease, as in the present case. 19 A fetal origin appears to be almost certain in 21 (32%) of the 67 described cases (including the present case), given that the diagnosis was made within the neonatal 13 6 4 --2 --Fryns 15 1 -1 ----Kapur 16 1 ---1 1 -Herman 17 1 ---1 -1 Qureshi 18 1 25 4 ---2 --Voisin 28 1 ---1 --Reisman 33 1 1 -----Barbet 34 1 ---1 --Medart 35 1 20 Neuroblastomas and other neuroblastic tumours are derived from cells of the neural crest, an early and transient developmental structure. Changes within the "cardiac neural crest" have been implicated in a wide variety of congenital heart lesions, from inflow lesions (tricuspid atresia, double inlet left ventricle) to outflow anomalies (tetralogy of Fallot, transposition of the great arteries, double outlet right ventricle, common arterial trunk) and aortic arch lesions (interrupted aortic arch, double aortic arch), as well as noncardiovascular anomalies of thymus, thyroid, and parathyroid gland.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] In the UK only 33 neonates were identified with neonatal neuroblastoma between 1986 and 1994, most of whom had stage 4S disease, as in the present case. 19 A fetal origin appears to be almost certain in 21 (32%) of the 67 described cases (including the present case), given that the diagnosis was made within the neonatal 13 6 4 --2 --Fryns 15 1 -1 ----Kapur 16 1 ---1 1 -Herman 17 1 ---1 -1 Qureshi 18 1 25 4 ---2 --Voisin 28 1 ---1 --Reisman 33 1 1 -----Barbet 34 1 ---1 --Medart 35 1 20 Neuroblastomas and other neuroblastic tumours are derived from cells of the neural crest, an early and transient developmental structure. Changes within the "cardiac neural crest" have been implicated in a wide variety of congenital heart lesions, from inflow lesions (tricuspid atresia, double inlet left ventricle) to outflow anomalies (tetralogy of Fallot, transposition of the great arteries, double outlet right ventricle, common arterial trunk) and aortic arch lesions (interrupted aortic arch, double aortic arch), as well as noncardiovascular anomalies of thymus, thyroid, and parathyroid gland.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenal tumors and adrenal haemorrhage can be diagnosed with USS and it has been reported that prenatal USS diagnosis of neuroblastoma results in a higher survival rate as it is identified at an early stage [47]. Adrenal haemorrhage results from multiple patho-physiological factors.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported cases of prenatally diagnosed extra-adrenal neuroblastoma invading spinal neural foramina and causing neurologic symptoms distal to the mass [20][21][22] . One reported the case of an infant found to have an intra-abdominal solid mass on ultrasonography at 31 weeks' gestation [22] .…”
Section: Discussionmentioning
confidence: 99%